Hubungan Pemerintah Desa Dengan BPD (Badan Permusyawaratan Desa) Dalam Penetapanperaturan Desa (Studi pada Desa Sooko Kecamatan Sooko Kabupaten Mojokerto) - Rusydianyah, Muhammad Faza Dzulfikar (Jurnal Administrasi Publik, 2015)
Abstract: Government Relations Village With BPD (Village Consultative Body) In the determination of the Village Peratuarn (Studies in Rural Sooko Sooko Mojokerto). Determination of village regulations is something that is very important for the survival of the rural communities and to the progress of the village. Because of this village of rules towards rural development will be determined. Therefore it is the duty of government and BPD village to accommodate the aspirations of the people in the village of rules. Aspirations of the people can be accommodated by involving Village Consultative Body in the Perdes Determination. Because basically they are and share their aspirations the people they represent. In the sense that the village of rules can be implemented directly touch people's needs so that the program Establishment of village regulations and planned to be launched, the public can participate as optimal as possible. Ideas as well as the idea of making the village regulations must be based on the interests and needs of the communities themselves in meeting their needs that support to national development. The ideas and the idea of village regulations so this will be accommodated in the Village Consultative Body (BPD) and will dimufakatkan together in village development forum so it can be well planned between the government and society. Therefore, in determining the success of the village is very dependent regulation harmonious relationship that exists between the village chief and BPD Keywords: Village Government Relations and Regulatory Determination of BPD in the Village Abstrak: Hubungan Pemerintah Desa Dengan BPD (Badan Permusyawaratan Desa) Dalam Penetapan Peratuarn Desa (Studi Pada Desa Sooko Kecamatan Sooko Kabupaten Mojokerto). Penetapan peraturan desa Â adalah sesuatu yang sangat penting bagi kelangsungan hidup masyarakat desa tersebut dan untuk kemajuan desa tersebut. Karena dari Penetapan peraturan desa inilah arah pembangunan desa akan ditentukan. Karena itu sudah menjadi kewajiban pemerintahan desa dan BPD untuk menampung aspirasi masyarakat dalam Penetapan peraturan desa. Ide-ide serta gagasan pembuatan peraturan desa harus berdasarkan pada kepentingan dan kebutuhan dari masyarakat desa itu sendiri di dalam memenuhi kebutuhannya yang menunjang terhadap pembangunan nasional. Ide-ide dan gagasan peraturan desa demikian inilah yang akan ditampung dalam Badan Permusyawaratan Desa (BPD) dan akan dimufakatkan bersama dalam musyawarah pembangunan desa sehingga dapat direncanakan dengan baik antara pemerintah dengan masyarakat. Oleh sebab itu keberhasilan dalam penetapan peraturan desa sangat bergantung hubungan yang harmonis yang terjalin antara Kepala Desa dan BPD Kata kunci: Hubungan Pemerintah Desa Dan BPD Dalam Penetapan Peraturan Desa